GE_GERICHTE P/2026/2017 vom 19. Oktober 2018 - GE Cour de justice (2018)
INJURE ; CONTRAINTE(DROIT PÉNAL) ; VOIES DE FAIT ; LÉSION CORPORELLE SIMPLE ; MENACE(DROIT PÉNAL) ; PEINE PÉCUNIAIRE ; TORT MORAL ; INDEMNITÉ(EN GÉNÉRAL) | CP.177.al1; CP.181; CP.126.al1; CP.123.al1.ch1; CP.180.al1; CP.47; CP.49.al1; CP.34.al1.leta; CP.34.al2.leta; CP.42.al1; CPP.433.al1; CPP.126.al1.leta; CPP.428.al3